Students Reading Habit, Writing Interest, and Translation Ability on Indonesian Contextual Phrases - Ridhwan, Moehamad (LINGUA: Jurnal Bahasa dan Sastra, 2014)
This study was aimed to find out if the students reading habit and writing interest had a significant correlation as well as gave a significant contribution to their translation ability on Indonesian contextual phrases. One hundred and seventy students of Sriwijaya University, PGRI University and state polytechnic of Sriwijaya took part as the samples. To estimate the correlation among the variables, a quantitative research method including a Pearson Product-Moment Correlation and Multiple Regression were used. The result showed that the correlation between students reading habit and their translation ability on Indonesian contextual phrases was 0.082 with the significant level of 0.287 which meant no significant correlation. The correlation between students writing interest and their translation ability on Indonesian contextual phrases was 0.109 with the significant level of 0.159 indicating also no significant correlation. When both students reading habit and writing interest were combined, the contribution to their translation ability on Indonesian contextual phrases was only 1.4% (R2 0.014) which was too little to be considered significant. Some qualitative explanations for the unexpected results were offered and the implications of the findings were accounted for.